(untitled) (Qawanin Jurnal Ilmu Hukum, 2024)
This research aims to examine the position of the triumvirate of ministers in the constitutional system of the Republic of Indonesia and examine the relationship between the triumvirate of ministers as executors of presidential duties in the State Ministry system of the Republic of Indonesia. The type of research used in this research is normative legal research. The research results show that the position of the triumvirate of ministers in the constitutional system of the Unitary State of the Republic of Indonesia has been regulated in the third amendment to the UUD NRI 1945, namely Article 8 paragraph (3) which regulates more detailed rules in the event that the President and Vice President are absent. Then the reason why the ministers of the Triumvirate carry out presidential duties is because they are considered to understand the ins and outs of government affairs. The solution offered by the author is that the President and the People’s Representative Council need to make derivative regulations for the implementation of Article 8 Paragraph (3) of the UUD NRI 1945 and a change needs to be made in Law Number 39 of 2008 concerning the Ministry of State Affairs. Abstrak: Penelitian ini bertujuan untuk mengkaji kedudukan triumvirat menteri dalam sistem ketatanegaraan Republik Indonesia dan mengkaji hubungan triumvirat menteri sebagai pelaksana tugas presiden dalam sistem Kementerian Negara Republik Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Hasil penelitian menunjukkan bahwa kedudukan triumvirat menteri dalam sistem ketatanegaraan Negara Kesatuan Republik Indonesia telah diatur dalam amandemen ketiga UndangUndang Dasar Negara Republik Indonesia Tahun 1945 yaitu Pasal 8 ayat (3) yang mengatur aturan lebih rinci dalam hal Presiden dan Wakil Presiden berhalangan. Kemudian yang menjadi alasan mengapa pelaksana tugas kepresiden adalah Menteri Triumvirat, karena mereka dianggap memahami seluk beluk urusan pemerintahan. Adapun solusi yang ditawarkan oleh Penulis yaitu Presiden Bersama Dewan Perwakilan Rakyat perlu membuat aturan turunan pelaksanaan Pasal 8 Ayat (3) UUD NRI Tahun 1945 dan perlu dilakukan suatu perubahan dalam Undang-Undang Nomor 39 Tahun 2008 Tentang Kementerian Negara.